Reflections on Ideological Consistency between Community-Based Research and Counselling Practice - Harris, Gregory E. (Canadian Journal of Counselling and Psychotherapy, 2009)
Community-based research (CBR) and counselling practice share multiple skill sets and ideological tenets. In addition, CBR offers an approach to research that can be highly conducive to effective counselling-related research. Despite these consistencies and benefits, counsellors and counselling students have underutilized this approach to research. This article highlights several ideological similarities shared between counselling practice and CBR, along with benefits for counsellors in adopting such a research approach.